PENILAIAN RISIKO TEKNOLOGI INFORMASI PADA SOFTWARE HOUSEMENGGUNAKAN METODE FMEA DAN KONTROL DARI FRAMEWORK ISO27001:2013 - Gita, Azam; Putra W., Bramada; Zuhri, M. Saifuddin; Abimanyu , Farhan; Tifara, Shelma; Puspitaningrum, Ari Cahaya; Fitrani, Laqma Dica (JURNAL PENELITIAN DAN KARYA ILMIAH LEMBAGA PENELITIAN UNIVERSITAS TRISAKTI, 2024)
This study aims to identify and analyze the risks faced by CV Trisula Medika Teknologi, a software house company in the health sector. The method used is Failure Mode and Effects Analysis (FMEA) to identify potential failures and the Risk Priority Number (RPN) to determine the priority of risk handling. The results showed that there were 14 potential failures identified. Three of them have high-priority risks: hardware component damage, software update failure, and source code bugs. Damage to hardware components can cause the system to stop and disrupt the company's business processes. Failure of software updates can make the system vulnerable to malware and virus attacks. The existence of bugs in the source code can cause the system to be unstable and potentially result in fatal errors. The conclusion of this research emphasizes the importance of conducting regular risk identification and analysis to manage risks effectively and efficiently. By identifying and analyzing risks regularly, companies can take appropriate preventive measures to minimize the impact of risks. This can help the company improve the quality of its products and services, and increase customer confidence.